2014
DOI: 10.1158/1055-9965.epi-14-0598
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of microRNA-21 in Colorectal Cancer: An Original Study and Individual Participant Data Meta-analysis

Abstract: Background: We aimed to systematically summarize the diagnostic and prognostic value of circulating/ tissue miR21 in patients with colorectal cancer.Methods: An original study was conducted to explore the potential value of circulating miR21 in colorectal cancer diagnosis and tissue miR21 in colorectal cancer prognosis. PUBMED and EMBASE were searched (to August, 2013) to identify eligible studies. To explore the diagnostic performance of circulating miR21, metaanalysis methods were used to pool sensitivity, s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…This may be due to the breakdown of the miRNA in the plasma samples. However, the majority of the previous studies in NSCLC did not examine the exosomal miRNAs separated from the plasma or serum, which would likely include the intact miRNA (7)(8)(9)(10)(11)(12)(13)(26)(27)(28)(29). In the present study, microarray-based expression profiling of miRNAs derived from exosomes in the plasma of 6 NSCLC patients with or without recurrence was employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the breakdown of the miRNA in the plasma samples. However, the majority of the previous studies in NSCLC did not examine the exosomal miRNAs separated from the plasma or serum, which would likely include the intact miRNA (7)(8)(9)(10)(11)(12)(13)(26)(27)(28)(29). In the present study, microarray-based expression profiling of miRNAs derived from exosomes in the plasma of 6 NSCLC patients with or without recurrence was employed.…”
Section: Discussionmentioning
confidence: 99%
“…From these results, miR-4257 and miR-21 were selected as recurrence-specific biomarkers for NSCLC patients. It has been reported that serum miR-21 is significantly associated with the promotion of tumor growth, proliferation and progression, and the response of cancer to chemotherapy (26). In an evaluation of clinicopathological significance, Wang et al reported that serum miR-21 expression was significantly correlated with advanced TNM stage and the presence of lymph node metastasis in NSCLC patients (27).…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies screened for microRNA with significantly different expressions using a microRNA microarray in a small sample size and then validated the results by qRT‐PCR in a larger sample size. Thus, numerous systematic reviews and meta‐analyses have described the diagnostic efficiencies of microRNA . Most of these studies reviewed only 1 microRNA, while others reviewed all microRNA and conducted meta‐analyses including all of the diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…One of most extensively investigated miRNA is miR-21 whom tissue expression was reported to be independently associated with poor prognosis by two meta-analyses (65,66). The first study demonstrating that high levels of serum (rather than tissue) miR-21 indicate a poor prognosis in patients with CRC, was published in 2013 by Toiyama and coauthors (67).…”
Section: Prognostic Role Of Circulating Mirnasmentioning
confidence: 99%